2019
DOI: 10.1128/aac.00372-19
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protease Inhibitors Containing C-5-Modifiedbis-Tetrahydrofuranylurethane and Aminobenzothiazole as P2 and P2′ Ligands That Exert Potent Antiviral Activity against Highly Multidrug-Resistant HIV-1 with a High Genetic Barrier against the Emergence of Drug Resistance

Abstract: Combination antiretroviral therapy has achieved dramatic reductions in the mortality and morbidity in people with HIV-1 infection. Darunavir (DRV) represents a most efficacious and well-tolerated protease inhibitor (PI) with a high genetic barrier to the emergence of drug-resistant HIV-1. However, highly DRV-resistant variants have been reported in patients receiving long-term DRV-containing regimens. Here, we report three novel HIV-1 PIs (GRL-057-14, GRL-058-14, and GRL-059-14), all of which contain a P2-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…There is only one difference: both GRL-077 and GRL-058 have C5-modified Tp-THF, while GRL-044 has unmodified (44) Tp-THF, strongly suggesting that the C5-modification significantly weakens the potency against HIV-1 NL4-3 , although the potency of GRL-077 and GRL-058 against various PI-resistant variants including HIV DRV R P10 and HIV DRV R P30 is comparable with that of GRL-044. Determination of thermal stability using the differential scanning fluorimetry employing SYPRO ® orange helps understand the specificity and binding force of protein and its ligand (19,29,31). The T m values of DRV and SQV, which were greater than those without agent and with AZT, were the lowest and those with GRL-037 and GRL-044 were further greater (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is only one difference: both GRL-077 and GRL-058 have C5-modified Tp-THF, while GRL-044 has unmodified (44) Tp-THF, strongly suggesting that the C5-modification significantly weakens the potency against HIV-1 NL4-3 , although the potency of GRL-077 and GRL-058 against various PI-resistant variants including HIV DRV R P10 and HIV DRV R P30 is comparable with that of GRL-044. Determination of thermal stability using the differential scanning fluorimetry employing SYPRO ® orange helps understand the specificity and binding force of protein and its ligand (19,29,31). The T m values of DRV and SQV, which were greater than those without agent and with AZT, were the lowest and those with GRL-037 and GRL-044 were further greater (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why both HIV 11MIX 037-1-WK40 and HIV 11MIX 044-1-WK40 were not sufficiently replicative in the homologous recombination-based selection assay could be due to the acquisition of A28S substitution. The A28S substitution has been seen in the selection assay of HIV-1 with a few PIs, such as TMC-126 (26), GRL-98065 (27), brecanavir (25), and GRL-1398 (12), and not with any of the currently available FDA-approved PIs except only in a few cases (28,29). Of note, however, the population size of HIV-1 in the present homologous recombinationbased selection assay is assumed to be significantly smaller than the size of HIV-1 variants such as polymorphic amino acid substitution-containing variants that reside in HIV-1-infected individuals, the appearance of mutations is affected by stochastic phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This compound had an EC 50 ranging from 1.6 nM to 30.7 nM. [70] Ali and collaborators, at the University of Massachusetts Medical School, developed a series of novel PIs having phenyloxazolidinone P2 ligands (35). SAR studies showed that the introduction of polar substituents, such as methylsulfonyl group at the 3-position of the phenyl ring as P2 ligand significantly increased in-vitro antiviral activity.…”
Section: Reverse Transcriptase Inhibitorsmentioning
confidence: 99%